2019
DOI: 10.3390/pathogens8020064
|View full text |Cite
|
Sign up to set email alerts
|

Piper betel Compounds Piperidine, Eugenyl Acetate, and Chlorogenic Acid Are Broad-Spectrum Anti-Vibrio Compounds that Are Also Effective on MDR Strains of the Pathogen

Abstract: The natural population of the aquatic environment supports a diverse aquatic biota and a robust seafood industry. However, this environment also provides an appropriate niche for the growth of pathogenic bacteria that cause problems for human health. For example, species of the genus Vibrio inhabit marine and estuarine environments. This genus includes species that are pathogenic to aquaculture, invertebrates, and humans. In humans, they can cause prominent diseases like gastroenteritis, wound infections, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The phytochemical profiles of the extracts tend to vary considerably in terms of CGA and CA content, but not in terms of caffeine. It should be noted that CGA, which has potential anti-MDR V. cholerae activity ( 22 24 ), was found in the most abundant phenolic compounds in the CP extract, which is consistent with previous findings ( 70 72 ). The productivity, chemical composition, and biological activity of coffee extract are all known to be influenced by the brewing process ( 73 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The phytochemical profiles of the extracts tend to vary considerably in terms of CGA and CA content, but not in terms of caffeine. It should be noted that CGA, which has potential anti-MDR V. cholerae activity ( 22 24 ), was found in the most abundant phenolic compounds in the CP extract, which is consistent with previous findings ( 70 72 ). The productivity, chemical composition, and biological activity of coffee extract are all known to be influenced by the brewing process ( 73 ).…”
Section: Discussionsupporting
confidence: 92%
“…The usefulness of determining the major active components against this bacterium led to a time-killing kinetics study, which revealed that CA had bactericidal activity against V. cholerae within 1 h of exposure. This is unexpected, because a previous study found that CGA from Piper betel plants had antimicrobial activity against MDR V. cholerae at a concentration of the MIC value of 5.5 ± 0.5 mg/mL ( 22 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…9). 114 Punicalagin (91) from pomegranate (Punica granatum Linn.) was reported against V. anguillarum at MIC 25 mg mL −1 .…”
Section: Antivibrio From Plantsmentioning
confidence: 99%
“…Another active phenolic compound widely found in natural food substances including betelvine is Chlorogenic acid. Chlorogenic acid is also endowed with broad spectrum antimicrobial efficacy [80], including those micro-organisms that are found during early dental plaque formation, such as S. mutans [81].…”
Section: Influence Of Betelvine Extract On Oral Pathogensmentioning
confidence: 99%